Revisited the localization of fortifications of the 18th century on the surroundings of village of Braha in Khmelnytsky region - Harlan, Oleksandr (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
The results of the survey of the territories of the village Braga in the Khmelnytsky region, which is in close proximity to Khotyn Fortress, are highlighted in this article. A general description of the sources that were the fortifications of the left bank of the Dnister River opposite the Khotyn Fortress according to the modern landscape, is presented.